Chartres, d’Autrikon à Autricum, cité des Carnutes : prémices et essor de l’urbanisation - Dominique Joly; Stéphane Willerval; Pauline Denat (Gallia)
Excavations carried out in Chartres during the last decade, systematically sequenced and dated thanks to ceramic studies, provide a collection of reference points for establishing the main stages that marked the town’s evolution during the 1st c. AD. Among these, two cemeteries predated the installation of the Roman city. Its road network and the buildings along it are a good marker for the phasing of its development. The public buildings were probably constructed from the middle of the 1st c. AD. The dating of the digging of the large ditch with embankments has for a long time been uncertain. It seems that it ought to be assigned to the 1st c. AD.